Nurse Behavior in Implementation of Diabetes Mellitus Education Based on Theory of Planned Behavior - Nadia Rohmatul Laili; Sulistiawati Sulistiawati; Ika Yuni Widyawati (Jurnal Ners, 2017)
Introductions: Education is the important component in self-management of Diabetes mellitus patients. Nurse as one of the health care provider should take active role in giving adequate education. The aim of this study were to analyze factors influencing nurse’s behavior in implementation of Diabetes mellitus education based on theory of planned behavior.Methods: This study used cross sectional design. Population in this study were all nurses in medicinal public hall whose were assigned to give education toward patients in 62 puskesmas induk in Surabaya city in 2016. Sampling technique used total sampling and 112 nurses obtained as samples. Variables in this study consist of attitude, subjective norm, perceived behavioral control (PBC), intention and practice in DM education. Data collection was using questionnaire and observation sheet and also analyzed using spearman rho with α 0,05.Results: Statistical analysis result shows there is significant relationship between attitudes, subjective norm, perceived behavioral control (PBC) toward intention with p value of 0,022; 0,048; dan 0,000 respectively and there is no significant relationship between intention and practice of Diabetes mellitus education with p value 0,194. Nurse’s attitudes, subjective norm, perceived behavioral control (PBC) had positive effect toward intention of Diabetes mellitus education but intention had no effect toward practice of Diabetes mellitus education in puskesmas.Conclusion: Theory of Planned Behavior (TPB) stated that individual behavior occurred because of intention that could be affected by attitude, subjective norm, and perceived behavioral control (PBC). Future study was expected to use qualitative approach, and related study regarding development of education media in Puskesmas.